Studi Komparatif Peran Platform Digital Dan Konten Dalam Mengintervensi Strategi Komunikasi Lembaga Swadaya Masyarakat Lingkungan di Indonesia - Mohamad Hafiz (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
In Indonesia, environmental conservation is still relatively poor on a global scale. This is based on data findings in the 2022 Environmental Performance Index (EPI) report, Indonesia received a score of 28.2 out of 100 and caused Indonesia to be ranked 164th out of 180 countries studied. The ideas and role of society in preserving the environment are represented through the existence of Non-Governmental Organizations (NGOs) which operate in the field of environmental conservation. This research aims to compare the roles of digital platforms and content in intervening in the communication strategies of five environmental NGOs in Indonesia. This research approach is qualitative with a comparative study type through a systematic literature review. As a result, WALHI and Greenpeace are the environmental NGOs with the most variety of content and digital platforms used. Meanwhile, WWF Indonesia has a variety of content, but is low in distribution on digital platforms. Lastly, YKAN and KEHATI are low in content variety as well as digital platform distribution.